2019
DOI: 10.1152/ajprenal.00487.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc deficiency induces hypertension by promoting renal Na+ reabsorption

Abstract: Zn2+ deficiency (ZnD) is a common comorbidity of many chronic diseases. In these settings, ZnD exacerbates hypertension. Whether ZnD alone is sufficient to alter blood pressure (BP) is unknown. To explore the role of Zn2+ in BP regulation, adult mice were fed a Zn2+-adequate (ZnA) or a Zn2+-deficient (ZnD) diet. A subset of ZnD mice were either returned to the ZnA diet or treated with hydrochlorothiazide (HCTZ), a Na+-Cl− cotransporter (NCC) inhibitor. To reduce intracellular Zn2+ in vitro, mouse distal convol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
(41 reference statements)
0
26
1
Order By: Relevance
“…In this review, the serum Zn level was decreased in pre-eclamptic women than normal controls; the mechanism how Zn deficiency causes pre-eclampsia is not clearly understood. However, animal model studies suggested that Zn deficiency may induce high blood pressure by promoting sodium reabsorption by increasing Na + -Cl − cotransporter expression [44]. Zn deficiency in prenatal and postnatal rats induces blood pressure derangement accompanied by cardiovascular and renal morphological and functional changes [45].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, the serum Zn level was decreased in pre-eclamptic women than normal controls; the mechanism how Zn deficiency causes pre-eclampsia is not clearly understood. However, animal model studies suggested that Zn deficiency may induce high blood pressure by promoting sodium reabsorption by increasing Na + -Cl − cotransporter expression [44]. Zn deficiency in prenatal and postnatal rats induces blood pressure derangement accompanied by cardiovascular and renal morphological and functional changes [45].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in spontaneous hypertension-prone rats, dietary zinc restriction exacerbated systolic blood pressure [ 102 ], whereas zinc supplementation attenuated blood pressure response [ 103 ]. Of interest, Williams et al revealed a possible mechanism of zinc related to blood pressure regulation, as an Na + -Cl − cotransporter (NCC) was found to be a zinc-regulated transporter upregulated in mice with zinc deficiency, and NCC upregulation contributed to increased blood pressure by stimulating renal sodium reabsorption [ 104 ]. In human studies, it has been reported that populations with low dietary zinc intake have a high prevalence of hypertension, and a possible inverse correlation between zinc levels and blood pressure has also been noted [ 105 , 106 ].…”
Section: Zinc Deficiency and Risk Factors For Cvdmentioning
confidence: 99%
“…However, inverse correlations of blood pressure and serum zinc have also been observed [20]. A recently published article has implicated zinc deficiency to hypertension in animal models [21]. In another study, excessive zinc intake elevated systemic blood pressure levels in animal models and was presumably associated with the oxidative stress [22].…”
Section: Introductionmentioning
confidence: 99%